Integrated reporting: Challenges, benefits and the research agenda - Jaspal, S. J. S. *; Mohamad, S.; Kamaljeet, K. (Primrose Hall Publishing Group, 2019)
This paper aims to explain the significance of Integrated Reporting (IR) for an organisation's survival and sustainability. It reviews and deliberates the level of importance of IR generally and in Malaysia; the readiness of Malaysia in addressing the next step of post International Financial Reporting Standards (IFRS) convergence; and the extent of effort towards IR in Malaysia. This paper attempts to enrich insights into the domain of IR and its interpolation with the underlying assumption of going concern in accounting. The stand taken by regulators, the benefits of IR and views that oppose IR are discussed and set the platform for the research agenda in the IR domain.